2012
DOI: 10.5539/jas.v4n2p201
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Rabbits Fed Diets Containing Different Levels of Energy and Mixture of Some Medicinal Plants

Abstract: A total number of 48 male growing New Zealand rabbits were used to study the effect of two different levels of ration energy supplemented with mixture of Lupinus albus L, Trigonella foenum-graecum L and Cassia senna L as feed additives. Rabbits were classified into four equal groups (G 1 -G 4 ). The 1 st and 3 rd groups received basal ration with 100 % and 90 % energy requirement and served as first and second control respectively. The 2 nd and the 4 th groups received basal ration with 100 % and 90 % energy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Meanwhile, Myrie et al (2008) showed that most feedstuffs contain anti-nutritional factors such as insoluble fibers, ligins, tannins and lectins, intake of these anti-nutritional factors reduced nutrient digestibility and increased endogenous protein losses, through increasing of intestinal mucus secretion. Data concerning with performance Table 4 in harmony with those reported by Asar et al (2010), Omer et al (2011), andOmer andBadr (2013) concluded that inclusion dried faba bean straw, strawberry by-products, pea straw, and corn-cob meal can be substituted for dried clover and barley in growing rabbit rations without any adverse effect on their performance. Also the present results in agreement with those found by García et al (1993) who showed that incorporation sugar beet pulp up to 15% did not effect on growth performance.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Meanwhile, Myrie et al (2008) showed that most feedstuffs contain anti-nutritional factors such as insoluble fibers, ligins, tannins and lectins, intake of these anti-nutritional factors reduced nutrient digestibility and increased endogenous protein losses, through increasing of intestinal mucus secretion. Data concerning with performance Table 4 in harmony with those reported by Asar et al (2010), Omer et al (2011), andOmer andBadr (2013) concluded that inclusion dried faba bean straw, strawberry by-products, pea straw, and corn-cob meal can be substituted for dried clover and barley in growing rabbit rations without any adverse effect on their performance. Also the present results in agreement with those found by García et al (1993) who showed that incorporation sugar beet pulp up to 15% did not effect on growth performance.…”
Section: Discussionsupporting
confidence: 78%
“…Also, Salwa et al (2000), Falcão-e-Cunha et al (2004), andSarhan (2005) noticed that inclusion of agriculture by-products in rabbit rations improved EE digestibility. Also, Omer and Badr (2013) found that OM, CF, EE, and NFE digestibilities were significantly (P < 0.05) improved with replacement Berseem hay by pea straw in rations at different levels of replacement (0, 25, 75, and 100%). Also, feeding 30% pea pods hulls diet had better nutritive value compared to control (Sarhan 2005).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Most of these active secondary metabolites are isoprene derivatives, flavonoids and glucosinolates. Reports on the effects of this group of feed additives on rabbit growth performance (Omer et al, 2012), antioxidant, and antibacterial activity (Al-Turki, 2007), meat quality (Cardinali et al, 2012), blood biochemical parameters (Al-Jowari, 2012), reproductive performance (El-Nattat and El-Kady, 2007) and doe milk production (Eiben et al, 2004) are still fairly scarce, however in growing rabbits, particularly weaners, digestive disturbances are the main cause of the morbidity and mortality that create important economic losses for rabbit farmers (Licois, 2004 andMarlier et al, 2006). Weaning is the period in which the bunnies are separated from their mothers, milk is substituted with solid feed, and the bunnies immune system is still immature (Carabaño et al, 2006 andGidenne et al, 2005).…”
mentioning
confidence: 99%